Applying in life the skills learned in sport: A grounded theory. (January 2019) - Kendellen, Kelsey; Camiré, Martin
Abstract: Objectives: The life skills process (i.e., sport to life) involves three interrelated stages: (a) life skills learning in sport, (b) life skills transfer, and (c) life skills application in at least one life domain beyond sport (Pierce, Gould, & Camiré, 2017). The purpose of the study was to examine how athletes apply in life the skills learned or refined in sport in order to develop new theoretical explanations for the third stage of the life skills process (i.e., application). Design: A grounded theory methodology (Corbin & Strauss, 2015). Method: Data collection occurred over 10 months, involving interviews, chronological charts, timelines, and journals with university intramural athletes ( n  = 13). Social agents ( n  = 29) playing key roles in the athletes' lives (e.g., parents, partners, work colleagues) were theoretically sampled and interviewed. Data analysis: Data analysis involved an iterative process of open coding, axial coding, and theoretical integration. Results: The substantive grounded theory is constructed on the core category of "mutually beneficial person-context regulations". Within the theory, skill application is framed as an ongoing process that involves four steps (a) decision-making, (b) application, (c) appraisal, and (d) adaptation. Conclusions: The substantive grounded theory puts forth theoretical explanations as to how athletes apply in their everyday lives the skills they deem to have learned in sport. Highlights: Substantive theory explains how athletes apply in life the skills learned in sport. Data collection involved interviews, charts, timelines, and journals over 10-months. Sample included athletes and their key social agents outside of sport. Athletes' interactions with social agents influence life skills application.